2011
DOI: 10.1002/lary.21451
|View full text |Cite
|
Sign up to set email alerts
|

The Gelfoam® plug: An alternative treatment for small eardrum perforations

Abstract: Aim: To examine if a Gelfoam V R plug in combination with surgical removal of the perforation edges could be an alternative to the widely accepted fat plug treatment for smaller ear drum perforations.Materials and Methods: A prospective study of 17 consecutive patients with persistent small ear drum perforations considered for myringoplasty. The perforations were central perforations 2 to 4 mm in diameter. Patient ages ranged from 6 to 83 years, and the operation was performed under general anesthesia with mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…It has been indicated that a Gelfoam 1 plug in minor myringoplasty surgery might have better results than using fascia or fat plugs [21] and that it is associated with shortened healing time in acute perforations [22]. After application of Gelfoam 1 an infiltration of neutrophils, fibroblasts and an angiogenesis have been described in the surrounding tissue and matrix [19].…”
Section: Gelfoam 1 As a Supporting Matrixmentioning
confidence: 98%
“…It has been indicated that a Gelfoam 1 plug in minor myringoplasty surgery might have better results than using fascia or fat plugs [21] and that it is associated with shortened healing time in acute perforations [22]. After application of Gelfoam 1 an infiltration of neutrophils, fibroblasts and an angiogenesis have been described in the surrounding tissue and matrix [19].…”
Section: Gelfoam 1 As a Supporting Matrixmentioning
confidence: 98%
“…Gelfoam patching was usually used to treat traumatic tympanic membrane perforations and chronic dry small perforations . However, in clinical outpatient setting, we observed that some perforations could heal rapidly while others failed to close.…”
mentioning
confidence: 78%
“…It is well known that the patch serves as a scaffold to guide migrating epithelium to close the eardrum perforation. Gelfoam is frequently utilised in otology because of its convenience in outpatient setting, but it is associated with varying clinical outcomes as some perforations heal rapidly while others fail to close and stay patent …”
Section: Discussionmentioning
confidence: 99%
“…[9] The functioning of several potential synthetic biodegradable eardrum grafts and non-degradable, microporous eardrum grafts was examined by Feenstra et al, both visually and histologically in experimental studies with animals. [10] In 2011, Nicklasson et al conducted a study of Gelfoam plug after freshening of TM, providing a success rate of 83%. [11] In 1992, Baldwin and Loftin conducted 115 cases of Gelfilm myringoplasty with an interlocking Gelfilm stent and obtained 94% closure.…”
Section: Biomaterials Used For Tympanic Membrane Repairmentioning
confidence: 99%